2014
DOI: 10.1038/ncomms6509
|View full text |Cite
|
Sign up to set email alerts
|

The K526R substitution in viral protein PB2 enhances the effects of E627K on influenza virus replication

Abstract: Host-adaptive strategies, such as the E627K substitution in the PB2 protein, are critical for replication of avian influenza A viruses in mammalian hosts. Here we show that mutation PB2-K526R is present in some human H7N9 influenza isolates, in nearly 80% of H5N1 human isolates from Indonesia and, in conjunction with E627K, in almost all seasonal H3N2 viruses since 1970. Polymerase complexes containing PB2-526R derived from H7N9, H5N1 or H3N2 viruses exhibit increased polymerase activity. PB2-526R also enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
160
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(165 citation statements)
references
References 58 publications
4
160
1
Order By: Relevance
“…Newly identified substitutions, such as S286G and S534F, mainly occur in combination with 627K and 591K and might further boost polymerase activity above the level of the E627K substitution alone. Correspondingly, the human-transmissible H3N2 and pH1N1 viruses have been reported to be dependent on multiple adaptive mutations (21,(44)(45)(46). Additionally, adaptation of the polymerase subunits is not limited to polymerase activity but might also help to circumvent the host innate immune response (18,33).…”
Section: Discussionmentioning
confidence: 99%
“…Newly identified substitutions, such as S286G and S534F, mainly occur in combination with 627K and 591K and might further boost polymerase activity above the level of the E627K substitution alone. Correspondingly, the human-transmissible H3N2 and pH1N1 viruses have been reported to be dependent on multiple adaptive mutations (21,(44)(45)(46). Additionally, adaptation of the polymerase subunits is not limited to polymerase activity but might also help to circumvent the host innate immune response (18,33).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of HPAI H7N9 viruses may represent an increased threat to human health, as the acquisition of a multi-basic cleavage site in HA is associated with increased pathogenicity in mammals (Hatta et al, 2001; Munster et al, 2010; Schrauwen et al, 2012; Suguitan et al, 2012). Sequence analysis of three human HPAI H7N9 isolates [A/Guangdong/17SF006/2017, A/Guangdong/17SF003/2016 (GD/3), and A/Taiwan/1/2017] revealed that A/Guangdong/17SF006/2017 and A/Taiwan/1/2017 possess the E627K mutation in the polymerase subunit PB2 protein (Ke et al, 2017), which confers efficient replication in mammals (Hatta et al, 2001; Subbarao et al, 1993), and that A/Taiwan/1/2017 has the K526R mutation in PB2, which contributes to enhance replication of H7N9 virus in combination with PB2-627K (Song et al, 2014). Moreover, the three human isolates encode the G186V mutation in HA (H3 numbering), which facilitates increased binding to human-type receptors (Dortmans et al, 2013; Ramos et al, 2013; Xiong et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic nature of the H7N9 virus population has been further emphasized by phylogenetic analyses which have identified considerable genetic diversity among H7N9 viruses and ongoing internal gene segment exchange with enzootic H9N2 viruses [17,18]. Internal genes including PB2 and NP have been identified as important determinants of avian virus pathogenicity and fitness in mammalian hosts [19][20][21][22] and ongoing H7N9 evolution in the avian reservoir may have contributed to changes in H7N9 epidemiology during the second wave. Continued reassortment in the avian reservoir could also allow for the emergence of novel H7N9 strains in subsequent outbreaks with increased pathogenicity or capacity for human-to-human transmission.…”
mentioning
confidence: 99%